2020
DOI: 10.31703/gmsr.2020(v-iii).05
|View full text |Cite
|
Sign up to set email alerts
|

Leadership styles and Its Impact on Employee Performance with a mediating effect of Organizational Commitment, An empirical study of NHA, Pakistan.

Abstract: The study was conducted to investigate the relationship between autocratic and democratic leadership on employee performance through the mediation of organizational commitment in National Highway Authority Islamabad head office. The inquiry was conducted in a natural working environment of an organization where respondents are situated/located, that is a filed study. Simple random sampling technique was used to carry out the research using structured questionnaires which were adopted from other researcher's st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Assefa (2020) study revealed that there is a significant relationship between democratic leadership style and teachers school commitment. Study findings of Alvi et. al.…”
Section: Democratic Leadership Style and Commitmentmentioning
confidence: 86%
“…Assefa (2020) study revealed that there is a significant relationship between democratic leadership style and teachers school commitment. Study findings of Alvi et. al.…”
Section: Democratic Leadership Style and Commitmentmentioning
confidence: 86%